Size composition, reproductive investment, and fecundity of red king crab (Paralithodes camtschaticus) in Finnmark fjords, 1994-2022 - Hjertaas, Haakon Winge (UiT Norges arktiske universitet, 2023)
The release of red king crab (Paralithodes camtschaticus) into the Barents Sea by Russian scientists in the 1960s had the goal of establishing a self-sustaining stock for the purpose of commercial harvest. The red king crab has been successfully established as a stock in Norwegian waters where it has become an important commercial resource in the eastern regions of Finnmark. The Norwegian red king crab fishery is separated into two different regimes to meet two management goals, with a free fishery west of North Cape (26ºE) and a quota regulated fishery east of North Cape. This study examines the general size composition of the red king crab, investigates the female reproductive strategy, factors affecting reproductive investment and fecundity over time from when the research fishery started in 1994 till present. The findings presented in this study are general decreasing trends in size composition for both males and ovigerous (roe carrying) females during the sampling period. Clear trends toward a reduction the size where 50% of females are ovigerous in all fjords and over years. Temporal and spatial variability in measured individual egg weight has been demonstrated, and a standardized ovigerous female crab with a 125 mm carapace length (CL) is overall less fecund, compared to previous studies. These changes in population size composition, size at maturity (OL50), reproductive investment and fecundity have been suggested to be result of heavy fishing pressure on large crabs of both sexes, as a result sperm limitation may occur due to low numbers of large males. The decrease in reproductive investment and fecundity could also be related to a reduction in availability of high-quality food items for the crabs.